Efforts to Improve Learning Outcomes in Solving Addition and Subtraction Problems with Concrete Objects Media in Mathematics Learning - Woro Tri Astuti (Universitas Sebelas Maret, 2022)
This study aims to describe the improvement of learning outcomes through the application of concrete object learning media in mathematics subjects of grade IV students. The type of research used in is Classroom Action Research (PTK). The subjects of the study were grade I students at sdn sapen manisrenggo klaten for the 2023/2024 academic year as many as 20 students as recipients of action, while those who provided action were researchers and homeroom teachers of class I. The data collection methods used were observation, tests every cycle and documentation. This class action research is carried out in two cycles where each cycle consists of planning, action, observation and reflection. The results stated that cognitive learning outcomes were seen from the first cycle of mathematics subjects from 20 students who completed 12 students and incomplete 8 students with a percentage of 60% did not meet the minimum limit of classical completeness, then in cycle II students who completed 17 out of 20 students and who.